Преимущества и недостатки тандемного метода обучения (сравнительный анализ применения тандемного метода в руководстве дипломной работой студентов, получающих дополнительную квалификацию «Переводчик в сфере профессиональной коммуникации») - Anosova N. E. (Modern education development: theory, techniques and practice, 2017)
The article deals with the concept of tandem training, which implies pair work of students aimed at achieving a specific learning goal, in which each partner alternately plays the role of a trainee and a teacher. The author describes the experience of applying the tandem training method at Peter the Great St. Petersburg Polytechnic University, in preparation for the final qualifying work by the students aspiring for the additional qualification "Translator in the field of professional communication". Participants of the tandem were graduate students of the program "Translator in the field of professional communication" and second year Master students majoring in translation and interpretation.
Keywords: перевод; магистратура; translation; тандемный метод; переводчик в сфере профессиональной коммуникации; tandem method; translator in the field of professional communication; master's degree